PENGARUH MEDIA SOSIAL TERHADAP KEPUTUSAN MEMILIH SEKOLAH DI ‘AISYIYAH BOARDING SCHOOL BANDUNG - DIAN CANDRA FATIHAH DIAN CANDRA FATIHAH; EUIS SANDRI MEILAWATI EUIS SANDRI MEILAWATI (EKBIS (Ekonomi & Bisnis), 2018)
This research to find out the The Influence Of Social Media On The Decesion For Choosing School In 'Aisyiyah Boarding School Bandung.This research is using descriptive verifikatif method.m The population in this research are 59 respondents, with Purpose Sampling techniques. Primary data in this study is obtained from questionnaires with Likert scale and statistically processed with SPSS version 25.0. The data analysis technique are simple linear regression and correlation between variables to prove the influence of social media on the decesion for choosing school in 'Aisyiyah Boarding School Bandung. Based on the research, it can be concluded that social media has a strong relationship with the decision for choosing school. As the value of correlation coeffisien of social media to the decision for choosing school is 0.616 means at a strong relation level. Then the hypothesis for the influence of social media on the decesion for choosing school in 'aisyiyah boarding school bandung has been received because it has value greater than t count > t table (5,901 > 1,672). Then the coefficient of determination is 37,9%. It means 37,9 % of the decision for choosing school is influenced by social media and the remaining 62,1% (100%-37,9%) is influenced by factors or other variabels that aren’t researched by the researcher.